Impacts of climate change on the distribution pattern of Himalayan Rhubarb (Rheum australe D. Don) in Nepal Himalaya - Babu Ram Paudel; Chandra Kanta Subedi; Suresh Kumar Ghimire; Dipesh Pyakurel; Meena Rajbhandari; Ram Prasad Chaudhary (PLoS ONE, 2025)
While there has been substantial consensus that climate change poses a severe threat to the Himalayan biota; we still lack comprehensive data on the potential impact of climate change on the important Himalayan medicinal plants connected with the livelihood of local people and the national economy. In this study, using MaxEnt, we modelled the distribution pattern of Rheum australe, a medicinal plant prioritized by the Government of Nepal for the nation’s economic prosperity, for the current as well as all four future projections (SSP126, SSP245, SSP370, and SSP585) to all the data available periods (2021–2040, 2041–2060, 2061–2080, and 2081–2100). In addition, we performed spatial overlay analysis to identify the optimum zones that could be developed as potential planting/conservation sites for R. australe in any of the projected future climate scenarios. Our results revealed that the suitability area of R. australe is expected to contract in all the scenarios and periods with a significant loss expected to occur in SSP585 for 2081–2100. On the individual district level, northwestern districts are expected to have a huge loss of suitable habitats in the future, while four districts: Jumla, Kalikot, Dolpa, and Jajarkot of the Karnali Province are expected to gain suitable habitats remarkably. Therefore, we suggest that the forests and rangelands of the four districts at an elevation range of 3300 m – 4,400 m could be developed as potential planting areas for commercial cultivation/for establishing genetic resource conservation centres. This finding thus has wider policy implications for both government and conservation organizations.